Feasibility of producing eco-friendly self-compacting mortar with municipal solid waste incineration bottom ash: A preliminary study - Hongrong Li; Hongyan Chu; Qun Wang; Jinhui Tang (Case Studies in Construction Materials, 2023)
Municipal solid waste incineration bottom ash (MSWI-BA) is a major by-product of municipal solid waste incineration, leading to severe shortages of landfill sites in metropolitan cities. To achieve the resource utilization of MSWI-BA, this study explored the feasibility of producing ecological self-compacting mortar (eco-SCM) with MSWI-BA to realize recycling in building materials. First, it focused on the impact of the MSWI-BA proportion on eco-SCM with regard to workability, physical performance, mechanical performance, and durability. Second, it explored changes in the micro pore structure and micromorphology of eco-SCM under the impact of MSWI-BA. Finally, it evaluated the environmental friendliness and cost-effectiveness of eco-SCM. It was found that, (1) the mechanical strength of eco-SCM added with MSWI-BA was decreased. Eco-SCM added with MSWI-BA had compressive strength, flexural strength, and dynamic elastic modulus within the range of 37.71–54.76 MPa, 13.89–20.93 MPa, and 21.05–35.84 GPa, respectively; (2) Due to the addition of MSWI-BA, the chloride permeability of eco-SCM were deteriorated, but its durability was still satisfactory; (3) The environmental friendliness and economic performance of eco-SCM could be significantly improved, because of the addition of MSWI-BA. The energy consumption, carbon emissions, and costs of eco-SCM added with MSWI-BA at 40 wt % were decreased by 10.26 %, 10.49 %, and 26.50 %, respectively; (4) Considering the changes in the workability, mechanical property, durability, environmental friendliness, and economic performance of eco-SCM added with MSWI-BA, MSWI-BA could be used to prepare eco-SCM and could be recycled in building materials.